FUNCTIONAL OUTCOME OF FIXATION OF TIBIA SCHATZKER TYPE II AND TYPE III FRACTURES UNDER ARTHROSCOPIC GUIDANCE - KARIM, MT; HASSAN , J; SAJID, M (Biological and Clinical Sciences Research Journal, 2023)
The tibial plateau fracture is a common type of orthopaedic fracture. An alternative to open reduction and internal fixation (ORIF) is arthroscopic-assisted reduction and internal fixation, which provides direct visualisation of the articular surface of the plateau, evaluation of the reduction of the articular surface, and management of any intra-articular pathology that may be associated with the reduction of the articular surface. This study aimed to determine the functional outcome of patients who received tibial fixation under arthroscopic supervision for Schatzker’s Type II and III tibial fractures. The research was conducted over six months in the Orthopaedic Surgical Department at Jinnah Hospital in Lahore from November 17, 2022, to May 17, 2023. Sixty patients met the inclusion criteria were recruited after obtaining written informed permission. A clinical and historical examination of each patient’s knees was conducted, followed by arthroscopy-guided internal reduction and repair of the tibial fracture under general anaesthesia. All patients received a post-operative rehabilitation regimen. At the three-month follow-up, standing AP radiographs were taken to examine the general alignment of the limbs, and Rasmussen score results were recorded. The average age of the patients was 46 years, and 63.3% were men and 36.7% were women. Schatzker grades II and III tibial plateau fractures were present in 53.3% and 46.7% of the patients, respectively. The mean Rasmussen clinical score was 27.33, indicating that 50 out of 60 patients had excellent recovery, nine out of 60 patients had good recovery, and one out of 60 patients had fair recovery. The mean Rasmussen radiological score was 7.36, indicating that 48 out of 60 patients had outstanding recovery, 11 out of 60 patients had good recovery, and one out of 60 patients had fair recovery. In conclusion, arthroscopic-assisted reduction and internal fixation is a good technique for treating young patients with Schatzker grades II-III tibial plateau fractures, and it enables control of co-existing injuries of intra-articular soft tissues, leading to faster recovery and greater patient satisfaction. However, having expertise in trauma and arthroscopic methods is important to carry out the procedure correctly.